A polymer-based composite transmission bearing and its preparation process
By setting a polymer matrix composite layer on the shaft matrix surface of the transmission bearing, and using the interaction of modified boron fibers and graphene microsheets, the wear resistance of the material is improved, the problem of transmission bearing wear is solved, the equipment life is extended and the equipment is improved Operational efficiency.
Patent Information
- Application Number
- CN202411571260.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Due to high load and continuous operation in the compressor, drive bearings are prone to wear problems, resulting in enlarged bearing gaps, offset centerlines, and damaged bearing chambers, thereby reducing operation efficiency and equipment life.
The polymer matrix composite layer processed with polymer matrix composite materials is provided on the surface of the shaft matrix, so that the shaft and the transmission bearing are connected by the polymer matrix composite layer to reduce wear consumption, and modified boron The interaction between fiber and graphene microsheets improves the tensile strength, notch impact strength and wear resistance of the material.
It effectively reduces the wear consumption of transmission bearings, extends the service life of the equipment, improves the operation efficiency of the compressor, and uses the early warning effect of the polymer matrix composite layer to detect wear conditions in advance to ensure timely replacement.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of bearings, and more specifically, to a polymer-based composite transmission bearing and a preparation process thereof. Background Art
[0002] Bearings are one of the important parts widely used in mechanical equipment, such as compressors, water pumps, motors, turbines, etc. In the actual application of compressors, due to the high load and continuous operation of the equipment, while providing continuous power, its transmission bearings also have the problem of wear. If friction occurs in the transmission bearing, it is easy to cause the bearing gap to expand, the center line to shift, and the bearing chamber to be damaged, resulting in a decrease in operating efficiency. In severe cases, the compressor cannot operate. Transmission bearings are generally made of metal, and the metal interaction between the shaft and the transmission bearing results in high friction loss. Therefore, studying a transmission bearing with good wear resistance has become a new topic to meet market demand and expand industry applications. Summary of the invention
[0003] In order to reduce the friction coefficient of a transmission bearing, the present application provides a polymer-based composite transmission bearing and a preparation process thereof.
[0004] In a first aspect, the present application provides a polymer-based composite transmission bearing, which adopts the following technical solution:
[0005] A polymer-based composite transmission bearing, wherein the surface of the shaft base is provided with a polymer-based composite layer, and the polymer-based composite layer is processed by using a polymer-based composite material;
[0006] The polymer-based composite material is mainly made of the following raw materials in parts by weight: 41.2-51.2 parts of polyphenylene sulfide resin, 15-25 parts of nylon 66 resin, 2-4 parts of compatibilizer, 0.4-0.6 parts of silane coupling agent, 9-11 parts of molybdenum disulfide, 14-16 parts of graphene microsheets, 4-6 parts of modified boron fiber, and 0.2-0.4 parts of antioxidant; the modified boron fiber is obtained by treating the boron fiber with 3-aminopropyl triethoxysilane, trimethylolpropane triacrylate, diethylenetriamine, trifluoroethyl acrylate, and hydroxymethyl acrylamide.
[0007] By adopting the above technical solution, a polymer-based composite layer is set on the surface of the shaft substrate, which changes the metal interaction between the shaft and the transmission bearing, so that the shaft and the transmission bearing are connected through the polymer-based composite layer, and are always in a close fit state, reducing wear and consumption. Moreover, after the polymer-based composite layer is worn out during long-term operation, the operating sound changes dramatically, from silent to harsh noise. At this time, it has entered a serious wear state and needs to be replaced, which has the effect of early warning.
[0008] The polymer-based composite layer of the present application is processed from a polymer-based composite material, and the raw materials of the polymer-based composite material are reasonably matched to improve the tensile strength and notched impact strength and reduce the friction coefficient. The tensile strength is greater than 200MPa and the notched impact strength is greater than 18KJ / m 2 , dry friction coefficient <0.15, wet friction coefficient <0.05, making it show the advantages of high tensile strength, high notch impact strength, low friction coefficient and good wear resistance, suitable for use in transmission bearings. Moreover, it does not affect the quality and operation of transmission bearings, improves ductility and flexibility, reduces wear, enhances wear resistance, reduces the number of repairs of transmission bearings, prolongs the life of compressors, and improves the operating efficiency of compressors.
[0009] The polymer-based composite material of the present application is based on polyphenylene sulfide resin and nylon 66 resin, and molybdenum disulfide is added to the raw material, which has good lubrication performance and increases the wear resistance of the polymer-based composite material. On this basis, graphene microsheets and modified boron fibers are added to the raw materials, and the force between the layers of the graphene microsheets is very small, which reduces the friction coefficient, and the boron fiber is modified to form a branch graft on the surface of the boron fiber, which not only greatly increases the number of branches, improves compatibility and dispersibility, but also introduces a large number of active groups such as siloxy, amide, tertiary amine, hydroxyl, ester, and fluorine into the branch graft, and under the action of a large number of active groups, the friction coefficient is reduced, the wear resistance is improved, and the polymer-based composite material exhibits better mechanical properties and wear resistance.
[0010] Optionally, the modified boron fiber is prepared by the following method:
[0011] Add boron fiber to ethanol at a temperature of 40-50°C, add 3-aminopropyltriethoxysilane, stir for 2-4 hours, then add trimethylolpropane triacrylate, stir for 28-32 hours, add diethylenetriamine, stir for 18-22 hours, add trifluoroethyl acrylate and methyl alcohol acrylamide, stir for 28-32 hours, filter, wash and dry to obtain modified boron fiber.
[0012] Optionally, the weight ratio of the boron fiber, 3-aminopropyl triethoxysilane, trimethylolpropane triacrylate, diethylenetriamine, trifluoroethyl acrylate, and methyl alcohol acrylamide is 10:(0.5-1.5):(2-4):(4-6):(6-8):(4-6).
[0013] By adopting the above technical scheme, 3-aminopropyl triethoxysilane is first grafted on the surface of the boron fiber, and an amino group is introduced, and then trimethylolpropane triacrylate is grafted by the reaction of the amino group and the carbon-carbon double bond, and an ester group is introduced, and the number of branches is increased synchronously, and then diethylenetriamine is grafted by the reaction of the ester group and the amine group, and a secondary amine group is introduced, and then trifluoroethyl acrylate and methyl alcohol acrylamide are grafted by the reaction of the secondary amine group and the carbon-carbon double bond, thereby obtaining a modified boron fiber. In the preparation method of the present application, grafting is carried out in steps, and the number of branches and active groups is continuously increased, which significantly increases the dispersibility of the modified boron fiber, and improves the wear resistance of the modified boron fiber, so that the modified boron fiber exhibits a better use effect, and also increases the tensile strength, notched impact strength and wear resistance of the polymer-based composite material, so that the polymer-based composite material exhibits a better comprehensive performance, and improves the mechanical properties and wear resistance of the transmission bearing.
[0014] Optionally, the weight ratio of the boron fiber to ethanol is 1:(8-12).
[0015] By adopting the above technical solution, the amount of ethanol added is optimized, so that the boron fiber is fully dispersed in the ethanol, which is convenient for the modification of the boron fiber and ensures the stability of the preparation of the modified boron fiber. In multiple implementation schemes, the weight ratio of the boron fiber to the ethanol is 1:10, and the weight ratio can also be set to 1:8, 1:9, 1:11, 1:12 as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0016] Optionally, the boron fibers have an average length of 1-5 mm and an average diameter of 50-200 μm.
[0017] By adopting the above technical scheme, the length and diameter of the boron fiber are optimized, which not only facilitates the selection of boron fiber and ensures the stability of the source of boron fiber, but also facilitates the dispersion of boron fiber in the raw materials, ensures the uniform distribution of boron fiber, and also ensures the quality and stability of polymer-based composite materials.
[0018] In multiple embodiments, the average length of the boron fiber is 3 mm and the average diameter is 100 μm. The average length can also be set to 1 mm, 2 mm, 4 mm, or 5 mm as needed. The average diameter can also be set to 50 μm, 80 μm, 130 μm, 150 μm, 180 μm, or 200 μm as needed, but the present invention is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Optionally, the tensile strength of the boron fiber is 3000-5000 MPa. In multiple embodiments, the tensile strength of the boron fiber is 4000 MPa, and the tensile strength can also be set to 3000 MPa, 3500 MPa, 4500 MPa, 5000 MPa as required, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] Optionally, the boron fiber is one of a carbon core boron fiber and a tungsten core boron fiber.
[0021] Optionally, the average particle size of the molybdenum disulfide is 1-5 μm, and the average radial width of the graphene microsheet is 1-20 μm and the average thickness is 5-25 nm.
[0022] By adopting the above technical scheme, the particle size of molybdenum disulfide, and the radial width and thickness of graphene microsheets are optimized, which not only facilitates the selection of molybdenum disulfide and graphene microsheets, ensures the stability of the sources of molybdenum disulfide and graphene microsheets, ensures the uniformity of the dispersion of molybdenum disulfide and graphene microsheets in the raw materials, but also ensures the mechanical properties and wear resistance of the polymer-based composite materials.
[0023] In multiple embodiments, the average particle size of molybdenum disulfide is 3 μm. The average particle size can also be set to 1 μm, 2 μm, 4 μm, or 5 μm as needed, but is not limited to the listed values. Other unlisted values within the numerical range are also applicable.
[0024] In multiple embodiments, the average radial width of the graphene microsheets is 10μm and the average thickness is 15nm. The average radial width can also be set to 1μm, 5μm, 8μm, 13μm, 15μm, 18μm, 20μm as needed. The average thickness can also be set to 5nm, 8nm, 10nm, 13nm, 18nm, 20nm, 23nm, 25nm as needed, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Optionally, the compatibilizer is a terpolymer of ethylene-methyl acrylate-methyl glycidyl ester;
[0026] The silane coupling agent is one or more of 3-aminopropyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, and vinyltrimethoxysilane;
[0027] The antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 626.
[0028] By adopting the above technical solution, the compatibilizer, silane coupling agent and antioxidant are optimized, which facilitates the selection of the compatibilizer, silane coupling agent and antioxidant. Moreover, the compatibilizer can effectively increase the bonding force between the raw materials, the silane coupling agent can be grafted to the surface of molybdenum disulfide and graphene microsheets and increase the dispersibility, and the antioxidant can reduce the oxidation deterioration of the polymer-based composite material, increase the storage time and extend the shelf life.
[0029] Optionally, the antioxidants are two kinds of antioxidants, namely antioxidant 1010 and antioxidant 168, and the weight ratio of antioxidant 1010 to antioxidant 168 is (1-3):(1-3). In multiple embodiments, the weight ratio of antioxidant 1010 to antioxidant 168 is 1:1, and the weight ratio can also be set to 1:2, 1:3, 2:1, 2:3, 3:1, 3:2 as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] Optionally, the polymer-based composite layer has a thickness of 0.3-0.5 mm.
[0031] By adopting the above technical solution, the thickness of the polymer-based composite layer is optimized, the cost increase due to excessive thickness is reduced, and the use effect is also reduced due to too small thickness, and the thickness is controlled within the range of 0.3-0.5mm, which can achieve the expected effect. In multiple implementation schemes, the thickness of the polymer-based composite layer is 0.4mm, and the thickness can also be set to 0.3mm, 0.35mm, 0.45mm, 0.5mm as needed, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0032] Optionally, the polymer-based composite material is prepared by the following method:
[0033] The polymer-based composite material is obtained by mixing polyphenylene sulfide resin, nylon 66 resin, a compatibilizer, a silane coupling agent, molybdenum disulfide, graphene microsheets, modified boron fibers and an antioxidant, heating and melting the mixture, and extruding and granulating the mixture.
[0034] By adopting the above technical solution, the preparation of polymer-based composite materials is facilitated.
[0035] Optionally, in the method for preparing a polymer-based composite material, the melting temperature is 360-380° C. In multiple embodiments, the melting temperature is 370° C., and the melting temperature can also be set to 360° C., 365° C., 375° C., 380° C. as required, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] In a second aspect, the present application provides a preparation process of the polymer-based composite transmission bearing, which adopts the following technical solution:
[0037] A preparation process of the polymer-based composite transmission bearing comprises the following steps:
[0038] S1, degreasing and cleaning the shaft matrix to obtain a degreased shaft matrix;
[0039] S2, passivating, cleaning, and drying the degreased shaft substrate to obtain a passivated shaft substrate;
[0040] S3, laser cutting the passivated shaft substrate to obtain a cutting shaft substrate of a preset size;
[0041] S4, repassivating, cleaning, and drying the cutting shaft substrate to obtain a repassivated shaft substrate;
[0042] S5. Cold-welding the polymer-based composite material on the surface of the re-passivated shaft substrate to form a polymer-based composite layer to obtain a transmission bearing.
[0043] By adopting the above technical solution, the preparation of the transmission bearing is facilitated.
[0044] In summary, this application has at least the following beneficial effects:
[0045] 1. The polymer-based composite transmission bearing of the present application has a polymer-based composite layer on the surface of the shaft substrate, so that the shaft and the transmission bearing are connected through the polymer-based composite layer to reduce wear and consumption. The polymer-based composite layer is processed from a polymer-based composite material, and the raw materials of the polymer-based composite material are reasonably matched, based on polyphenylene sulfide resin and nylon 66 resin, combined with molybdenum disulfide, and on this basis, graphene microsheets and modified boron fibers are added, and the interaction between graphene microsheets and modified boron fibers is used to improve the tensile strength and notched impact strength, and reduce the friction coefficient, with tensile strength>200MPa and notched impact strength>18KJ / m 2 , dry friction coefficient <0.15, wet friction coefficient <0.05, so that the polymer-based composite material exhibits the advantages of high tensile strength, high notch impact strength, small friction coefficient and good wear resistance. It is suitable for use in transmission bearings, improving ductility, flexibility, wear resistance, reducing the number of repairs, extending the life of the compressor, and improving the operating efficiency of the compressor.
[0046] 2. In the preparation method of the modified boron fiber of the present application, 3-aminopropyltriethoxysilane is first grafted on the surface of the boron fiber, then trimethylolpropane triacrylate is grafted, then diethylenetriamine is grafted, and then trifluoroethyl acrylate and methyl alcohol acrylamide are grafted. The mutual coordination of each step is utilized to carry out the grafting in steps, and the amount of branching and the amount of active groups are continuously increased. In addition, siloxy groups, amide groups, tertiary amine groups, hydroxyl groups, ester groups, fluorine groups, etc. are introduced to enhance the compatibility, dispersibility and wear resistance of the modified boron fiber, increase the tensile strength and notched impact strength of the polymer-based composite material, reduce the friction coefficient, and make the polymer-based composite material exhibit better mechanical properties and wear resistance. DETAILED DESCRIPTION
[0047] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.
[0048] Preparation Example
[0049] Preparation Example 1
[0050] A modified boron fiber is prepared by the following method:
[0051] At a speed of 400r / min and a temperature of 45°C, add 10g of boron fiber to 100g of ethanol and stir for 10min. Add 1g of 3-aminopropyltriethoxysilane and stir for 3h. Then add 2.7g of trimethylolpropane triacrylate and stir for 30h. Add 5.1g of diethylenetriamine and stir for 20h. Add 7g of trifluoroethyl acrylate and 4.6g of methyl alcohol acrylamide and stir for 30h. Then filter and wash with ethanol 3 times, using 50g of ethanol each time, and then dry to obtain modified boron fiber.
[0052] The boron fiber is a carbon core boron fiber, and the average length of the carbon core boron fiber is 3 mm, the average diameter is 100 μm, and the tensile strength is 4000 MPa.
[0053] Preparation Example 2
[0054] A modified boron fiber is prepared by the following method:
[0055] At a speed of 400r / min and a temperature of 45°C, add 10g of boron fiber to 100g of ethanol and stir for 10min. Add 0.5g of 3-aminopropyltriethoxysilane and stir for 2h. Then add 4g of trimethylolpropane triacrylate and stir for 32h. Add 4g of diethylenetriamine and stir for 18h. Add 6g of trifluoroethyl acrylate and 6g of methyl alcohol acrylamide and stir for 32h. Then filter and wash with ethanol 3 times, using 50g of ethanol each time, and then dry to obtain modified boron fiber.
[0056] The boron fiber is a carbon core boron fiber, and the average length of the carbon core boron fiber is 3 mm, the average diameter is 100 μm, and the tensile strength is 4000 MPa.
[0057] Preparation Example 3
[0058] A modified boron fiber is prepared by the following method:
[0059] At a speed of 400r / min and a temperature of 45°C, add 10g of boron fiber to 100g of ethanol and stir for 10min. Add 1.5g of 3-aminopropyltriethoxysilane and stir for 4h. Then add 2g of trimethylolpropane triacrylate and stir for 28h. Add 6g of diethylenetriamine and stir for 22h. Add 8g of trifluoroethyl acrylate and 4g of methyl alcohol acrylamide and stir for 28h. Then filter and wash with ethanol 3 times, using 50g of ethanol each time, and then dry to obtain modified boron fiber.
[0060] The boron fiber is a carbon core boron fiber, and the average length of the carbon core boron fiber is 3 mm, the average diameter is 100 μm, and the tensile strength is 4000 MPa.
[0061] Example
[0062] Table 1 Amount of each raw material used in polymer-based composite materials (unit: g)
[0063]
[0064] Example 1
[0065] A polymer-based composite transmission bearing, the transmission bearing comprises a shaft base, a polymer-based composite layer is arranged on the surface of the shaft base, the thickness of the polymer-based composite layer is 0.4 mm, the polymer-based composite layer is processed by polymer-based composite materials, and the raw materials and raw material ratios of the polymer-based composite materials are shown in Table 1.
[0066] Among them, the polyphenylene sulfide resin is selected from polyphenylene sulfide resin P0833A; the nylon 66 resin is selected from nylon 66 resin EP-158; the compatibilizer is ethylene-methyl acrylate-methyl glycidyl ester ternary random copolymer, and is selected from AX8900 of Dongguan Shenghao Plastic Raw Materials Co., Ltd.; the silane coupling agent is 3-aminopropyltriethoxysilane; the average particle size of molybdenum disulfide is 3μm; the average radial width of the graphene microsheets is 10μm and the average thickness is 15nm; the antioxidants are antioxidant 1010 and antioxidant 168, and the weight ratio of antioxidant 1010 to antioxidant 168 is 1:1; the modified boron fiber is prepared by the method of Preparation Example 1.
[0067] A preparation process of a polymer-based composite transmission bearing comprises the following steps:
[0068] S0. Add nylon 66 resin, compatibilizer, silane coupling agent, molybdenum disulfide, graphene microsheets, modified boron fiber, and antioxidant to polyphenylene sulfide resin, and stir for 10 minutes. Then heat to 370°C for melting, extrude and granulate to obtain a polymer-based composite material for standby use.
[0069] S1. Degreasing the shaft base to remove grease on the surface of the shaft base, and cleaning to obtain a degreased shaft base.
[0070] The shaft base is made of steel, specifically 45# steel.
[0071] S2. Immerse the degreased shaft substrate in a sodium dichromate aqueous solution and perform passivation treatment for 10 minutes to form a chromate passivation film on the surface of the degreased shaft substrate. Wash and dry the degreased shaft substrate to obtain a passivated shaft substrate.
[0072] The weight ratio of the degreased shaft substrate and the sodium dichromate aqueous solution is 1:50, and the mass concentration of sodium dichromate in the sodium dichromate aqueous solution is 0.5%.
[0073] S3. Laser cutting the passivated shaft substrate to obtain a cutting shaft substrate of a preset size.
[0074] S4. Immerse the cutting shaft substrate in a sodium dichromate aqueous solution and perform a repassivation treatment for 10 minutes to form a chromate passivation film on the surface of the cutting shaft substrate. Wash and dry the substrate to obtain a repassivated shaft substrate.
[0075] Among them, the weight ratio of the cutting shaft substrate and the sodium dichromate aqueous solution is 1:50, and the mass concentration of sodium dichromate in the sodium dichromate aqueous solution is 0.5%.
[0076] S5. Cold-welding the polymer-based composite material on the surface of the re-passivated shaft substrate to form a polymer-based composite layer to obtain a transmission bearing.
[0077] Among them, cold welding uses a cold welding machine, and the cold welding process of the cold welding machine is charging and discharging, with a cycle of 10 -3 s, discharge time is 10 -6 s. Cold welding is performed by using capacitor energy storage and high-frequency pulse instantaneous current release. At this time, the contact part between the polymer-based composite material and the cutting shaft substrate is heated, and the polymer-based composite material is melted and transitioned to the surface of the cutting shaft substrate, and diffused and infiltrated into the cutting shaft substrate to achieve tight bonding. At the same time, due to the short interval between the two discharge times and the instantaneous melting, the cutting shaft substrate can diffuse the heat to the outside, and there will be no heat accumulation, no volatilization of the polymer-based composite material, and the cutting shaft substrate can produce a strong diffusion layer, increase the bonding force of the polymer-based composite layer, and reduce the possibility of shedding.
[0078] Example 2
[0079] A polymer-based composite transmission bearing, which differs from Example 1 in that the raw material ratio of the polymer-based composite material of the polymer-based composite transmission bearing is different, and the raw material ratio is shown in Table 1.
[0080] Example 3
[0081] A polymer-based composite transmission bearing, which differs from Example 1 in that the raw material ratio of the polymer-based composite material of the polymer-based composite transmission bearing is different, and the raw material ratio is shown in Table 1.
[0082] Example 4
[0083] A polymer-based composite transmission bearing, which differs from Example 1 in that the source of the modified boron fiber in the raw materials of the polymer-based composite material of the polymer-based composite transmission bearing is different, and the modified boron fiber is prepared by the method of Preparation Example 2.
[0084] Example 5
[0085] A polymer-based composite transmission bearing, which differs from Example 1 in that the source of the modified boron fiber in the raw materials of the polymer-based composite material of the polymer-based composite transmission bearing is different, and the modified boron fiber is prepared by the method of Preparation Example 3.
[0086] Comparative Example
[0087] Comparative Example 1
[0088] A polymer-based composite transmission bearing, which differs from Example 1 in that an equal amount of molybdenum disulfide is used to replace graphene microsheets and modified boron fibers in the raw materials of the polymer-based composite material of the polymer-based composite transmission bearing.
[0089] Comparative Example 2
[0090] A polymer-based composite transmission bearing, which differs from Example 1 in that an equal amount of graphene microsheets is used to replace modified boron fibers in the raw materials of the polymer-based composite material of the polymer-based composite transmission bearing.
[0091] Comparative Example 3
[0092] A polymer-based composite transmission bearing, which differs from Example 1 in that an equal amount of boron fibers are used to replace graphene microsheets and modified boron fibers in the raw materials of the polymer-based composite material of the polymer-based composite transmission bearing.
[0093] Comparative Example 4
[0094] A polymer-based composite transmission bearing is different from Example 1 in that an equal amount of boron fiber is used to replace modified boron fiber in the raw material of the polymer-based composite material of the polymer-based composite transmission bearing.
[0095] Comparative Example 5
[0096] A polymer-based composite transmission bearing, which differs from Example 1 in that in the raw materials of the polymer-based composite material of the polymer-based composite transmission bearing, in the modified boron fiber preparation method, an equal amount of 3-aminopropyltriethoxysilane is used to replace trimethylolpropane triacrylate, diethylenetriamine, trifluoroethyl acrylate, and hydroxymethyl acrylamide.
[0097] Comparative Example 6
[0098] A polymer-based composite transmission bearing, which differs from Example 1 in that in the raw materials of the polymer-based composite material of the polymer-based composite transmission bearing, in the preparation method of the modified boron fiber, an equal amount of vinyltrimethoxysilane is used to replace hydroxymethyl acrylamide and trifluoroethyl acrylate.
[0099] Comparative Example 7
[0100] A polymer-based composite transmission bearing, which differs from Example 1 in that in the raw materials of the polymer-based composite material of the polymer-based composite transmission bearing, in the preparation method of the modified boron fiber, an equal amount of trifluoroethyl acrylate is used to replace hydroxymethyl acrylamide.
[0101] Comparative Example 8
[0102] A polymer-based composite transmission bearing, which differs from Example 1 in that, in the raw materials of the polymer-based composite material of the polymer-based composite transmission bearing, in the preparation method of the modified boron fiber, an equal amount of hydroxymethyl acrylamide is used to replace trifluoroethyl acrylate.
[0103] Performance Testing
[0104] (1) The polymer-based composite materials obtained in step S1 of Examples 1-5 and Comparative Examples 1-8 were respectively taken, and the tensile strength and notched impact strength of the polymer-based composite materials were tested according to GB / T1040.1-2018 and GB / T1043.1-2008. The test results are shown in Table 2.
[0105] (2) The transmission bearings obtained in Examples 1-5 and Comparative Examples 1-8 were respectively taken, and the dry friction coefficient and wet friction coefficient of the polymer-based composite layer of the transmission bearings were tested according to GB / T3960-2016. The test results are shown in Table 2.
[0106] Table 2 Test results
[0107]
[0108] It can be seen from Table 2 that the polymer-based composite material of the present application has high tensile strength and notched impact strength, with a tensile strength of 205-216 MPa and a notched impact strength of 18.9-19.8 KJ / m 2 Moreover, the polymer-based composite layer of the present application has a relatively low dry friction coefficient and a relatively low wet friction coefficient, the dry friction coefficient is 0.11-0.14, and the wet friction coefficient is 0.02-0.04. As a result, the polymer-based composite material exhibits the advantages of high tensile strength, high notched impact strength, low friction coefficient, and good wear resistance, effectively reducing the wear of the transmission bearing and extending the service life.
[0109] Comparative Examples 1-4 are compared. In the raw materials of the polymer-based composite material of Comparative Example 1, no graphene microsheets and boron fibers are added; in the raw materials of the polymer-based composite material of Comparative Example 2, graphene microsheets are added; in the raw materials of the polymer-based composite material of Comparative Example 3, boron fibers are added; in the raw materials of the polymer-based composite material of Comparative Example 4, graphene microsheets and boron fibers are added. It can be seen that adding graphene microsheets and boron fibers to the raw materials of the polymer-based composite material can significantly increase the tensile strength and notched impact strength.
[0110] Example 1 is compared with Comparative Example 4. Boron fiber is added to the raw material of the polymer-based composite material of Comparative Example 4; modified boron fiber is added to the raw material of the polymer-based composite material of Example 1. It can be seen that the modification of boron fiber can effectively increase the interaction between the modified boron fiber and the raw material, and further improve the tensile strength and notched impact strength, and notch impact strength, and notch impact strength, and notch impact strength, and notch impact strength, and notch impact strength, but also not only compensate for the influence of boron fiber on friction coefficient, but also reduce friction coefficient and increase wear resistance.
[0111] Example 1 is compared with comparative examples 5-8. The modified boron fiber of comparative example 5 is obtained by treating the boron fiber with 3-aminopropyl triethoxysilane; the modified boron fiber of comparative example 6 is obtained by treating the boron fiber with 3-aminopropyl triethoxysilane, trimethylolpropane triacrylate, diethylenetriamine, and vinyl trimethoxysilane; the modified boron fiber of comparative example 7 is obtained by treating the boron fiber with 3-aminopropyl triethoxysilane, trimethylolpropane triacrylate, diethylenetriamine, and trifluoroethyl acrylate; the modified boron fiber of comparative example 8 is obtained by treating the boron fiber with 3-aminopropyl triethoxysilane, trimethylolpropane triacrylate, diethylenetriamine, and hydroxymethyl acrylamide; the modified boron fiber of embodiment 1 is obtained by treating the boron fiber with 3-aminopropyl triethoxysilane, trimethylolpropane triacrylate, diethylenetriamine, trifluoroethyl acrylate, and hydroxymethyl acrylamide. It can be seen from this that in the preparation method of the modified boron fiber, 3-aminopropyl triethoxysilane, trimethylolpropane triacrylate, diethylenetriamine, trifluoroethyl acrylate, and hydroxymethyl acrylamide are used to treat the boron fiber to form branched grafts on the surface of the boron fiber, which not only increases the number of branches, but also introduces a large number of active groups such as siloxy, amide, tertiary amine, hydroxyl, ester, and fluorine groups into the branched grafts, greatly improving the dispersibility of the boron fiber, and under the action of the active groups, reducing the friction coefficient, improving the wear resistance, and making the polymer-based composite material exhibit better comprehensive performance.
[0112] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. A polymer-based composite transmission bearing, characterized in that: The transmission bearing comprises a shaft base, the surface of which is provided with a polymer-based composite layer, and the polymer-based composite layer is processed by using a polymer-based composite material; The polymer-based composite material is made of the following raw materials in parts by weight: 41.2-51.2 parts of polyphenylene sulfide resin, 15-25 parts of nylon 66 resin, 2-4 parts of a compatibilizer, 0.4-0.6 parts of a silane coupling agent, 9-11 parts of molybdenum disulfide, 14-16 parts of graphene microsheets, 4-6 parts of modified boron fiber, and 0.2-0.4 parts of an antioxidant; the modified boron fiber is obtained by treating the boron fiber with 3-aminopropyl triethoxysilane, trimethylolpropane triacrylate, diethylenetriamine, trifluoroethyl acrylate, and hydroxymethyl acrylamide; The modified boron fiber is prepared by the following method: Add boron fiber to ethanol at a temperature of 40-50°C, add 3-aminopropyl triethoxysilane, stir for 2-4 hours, then add trimethylolpropane triacrylate, stir for 28-32 hours, add diethylenetriamine, stir for 18-22 hours, add trifluoroethyl acrylate and methyl alcohol acrylamide, stir for 28-32 hours, filter, wash, and dry to obtain modified boron fiber; The weight ratio of the boron fiber, 3-aminopropyl triethoxysilane, trimethylolpropane triacrylate, diethylenetriamine, trifluoroethyl acrylate and methyl alcohol acrylamide is 10:(0.5-1.5):(2-4):(4-6):(6-8):(4-6).
2. A polymer-based composite transmission bearing according to claim 1, characterized in that: The weight ratio of the boron fiber to ethanol is 1:(8-12).
3. The polymer-based composite transmission bearing according to claim 1, characterized in that: The boron fibers have an average length of 1-5 mm and an average diameter of 50-200 μm.
4. The polymer-based composite transmission bearing according to claim 1, characterized in that: The average particle size of the molybdenum disulfide is 1-5 μm, and the average radial width of the graphene microsheet is 1-20 μm and the average thickness is 5-25 nm.
5. The polymer-based composite transmission bearing according to claim 1, characterized in that: The compatibilizer is a terpolymer of ethylene-methyl acrylate-methyl glycidyl ester; The silane coupling agent is one or more of 3-aminopropyltriethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, and vinyltrimethoxysilane; The antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 626.
6. The polymer-based composite transmission bearing according to claim 1, characterized in that: The thickness of the polymer-based composite layer is 0.3-0.5 mm.
7. The polymer-based composite transmission bearing according to claim 1, characterized in that: The polymer-based composite material is prepared by the following method: The polymer-based composite material is obtained by mixing polyphenylene sulfide resin, nylon 66 resin, a compatibilizer, a silane coupling agent, molybdenum disulfide, graphene microsheets, modified boron fibers and an antioxidant, heating and melting the mixture, and extruding and granulating the mixture.
8. A process for preparing a polymer-based composite transmission bearing according to any one of claims 1 to 7, characterized in that: The steps include: S1, degreasing and cleaning the shaft matrix to obtain a degreased shaft matrix; S2, passivating, cleaning, and drying the degreased shaft substrate to obtain a passivated shaft substrate; S3, laser cutting the passivated shaft substrate to obtain a cutting shaft substrate of a preset size; S4, repassivating, cleaning, and drying the cutting shaft substrate to obtain a repassivated shaft substrate; S5. Cold-welding the polymer-based composite material on the surface of the re-passivated shaft substrate to form a polymer-based composite layer to obtain a transmission bearing.
Citation Information
Patent Citations
High-weather-resistance environment-friendly high polymer material and preparation method thereof
CN112538263A
Preparation method of recyclable wear-resistant high-thermal-conductivity nylon 66 composite material
CN112646370A